2017
DOI: 10.1080/02699931.2017.1359015
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking emotions: how 3–12-month-old infants use the facial expressions and eyes of a model

Abstract: While there is an extensive literature on the tendency to mimic emotional expressions in adults, it is unclear how this skill emerges and develops over time. Specifically, it is unclear whether infants mimic discrete emotion-related facial actions, whether their facial displays are moderated by contextual cues and whether infants' emotional mimicry is constrained by developmental changes in the ability to discriminate emotions. We therefore investigate these questions using Baby-FACS to code infants' facial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…Although the extant literature on processing of dynamic facial expressions of emotion is limited, these findings are generally in line with previous data suggesting that by 7 months of age, infants exhibit scanning patterns that take into account the critical features of dynamic emotional expressions. Soussignan et al [ 38 ] found that while 3-month-old infants exhibited similar scanning patterns across multiple expressions, 7-month-olds exhibited differential scanning of facial features across expressions (e.g., increased fixations towards the eyes of fearful, angry, and sad faces compared to happy faces, fearful compared to neutral faces, and increased fixations towards the mouth of happy faces compared to all other expressions). Similarly, adults typically allocate attention towards different facial features depending on the emotion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the extant literature on processing of dynamic facial expressions of emotion is limited, these findings are generally in line with previous data suggesting that by 7 months of age, infants exhibit scanning patterns that take into account the critical features of dynamic emotional expressions. Soussignan et al [ 38 ] found that while 3-month-old infants exhibited similar scanning patterns across multiple expressions, 7-month-olds exhibited differential scanning of facial features across expressions (e.g., increased fixations towards the eyes of fearful, angry, and sad faces compared to happy faces, fearful compared to neutral faces, and increased fixations towards the mouth of happy faces compared to all other expressions). Similarly, adults typically allocate attention towards different facial features depending on the emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Parents of infants were contacted from an internal database via phone and email regarding participation in the current study. The sample size was determined by a power analysis using G*Power 3 software (Version 3.1.9.3, Heinrich Heine University, Düsseldorf, Germany) [ 41 ], to ensure sufficient power to detect a medium effect in the within-between analysis of variance (ANOVA) interaction (given the statistical significance criterion of 0.05, based on previous data; [ 38 ]). An additional 11 participants were tested, but their data were excluded because they did not complete the task due to fussiness (leading either to poor calibration at the start of the task, or inattention during the task; n = 5), technical difficulties with the eye tracking equipment ( n = 5), or they looked at the face for less than 1000 ms for both trials showing the same emotion ( n = 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an exploratory portion of the current study, infants' affective responses to facial expressions were investigated. Affective facial reactions have been studied extensively in adults using the Facial Action Coding System (FACS), which is an anatomically based Table 1 for a list of AUs have been commonly indicated as related to specifically positive or specifically negative facial displays (Camras et al, 2007;Dondi et al, 2007;Fogel, Hsu, Shapiro, Nelson-Goens, & Secrist, 2006;Kohut, Pillai Riddell, Flora, & Oster, 2012;Longfier et al, 2016;Mendes & Seidl-De-Moura, 2014;Messinger, Cassel, Acosta, Ambadar, & Cohn, 2008;Messinger, Mahoor, Chow, & Cohn, 2009;Soussignan et al, 2017)). Using the Baby FACS system, researchers have found that infants display a constellation of AUs in response to negative experiences, such as immunization pain (Kohut et al, 2012), novel foods (Longfier et al, 2016), arm restraint, and fear-eliciting situations (Camras et al, 2007).…”
Section: Do Infants' Affective Responses Differ For Fearful and Angrymentioning
confidence: 99%
“…Although the majority of studies using Baby FACS have focused on infants' affective responses to negative situations, one study asked how infants would respond to images of facial expressions. Soussignan et al (2017) presented 3-, 7-, and 12-month-old infants with virtual models of male and female faces displaying dynamic emotional expressions. Infant expressions were hand-coded using BabyFACS for clusters of AUs representing prototypical expressions and for AUs related to general negative affective responses.…”
Section: Do Infants' Affective Responses Differ For Fearful and Angrymentioning
confidence: 99%